2012
DOI: 10.5402/2012/624253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcomes of Hair Dye Poisoning in a Teaching Hospital in Nellore

Abstract: Demographic profiles, volume consumed, time to hospitalization, clinical presentation, laboratory findings, treatment details, and outcomes of patients with hair dye poisoning were analyzed to assess the effect of Super Vasmol 33. The efficacy of methylprednisolone as compared to hydrocortisone in patients was also investigated. Findings show that there are significant differences in the clinical profiles laboratory markers such as markers of leukocytosis, rhabdomyolysis, and hepatitis among patients who consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 8 publications
3
28
1
Order By: Relevance
“…Toxic effects of these ingredients could have had additive effect in the patient (Chandran et al, 2012). The combined effect of the individual compounds may be responsible for its significant morbidity and mortality (Kondle et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Toxic effects of these ingredients could have had additive effect in the patient (Chandran et al, 2012). The combined effect of the individual compounds may be responsible for its significant morbidity and mortality (Kondle et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PPD when ingested are serious and may cause cervicofacial edema, mucosal injury, respiratory distress, acute renal failure, rhabdomyolysis, and myocardial injury, cardiotoxicity and arrhythmias as well as atrophy of the optic nerve resulting in blindness in a patient who ingested an estimated amount of 7 g paraphenylenediamine and cause death (Bhargava & Matthew, 2007;Chandran et al, 2012;Kondle, Pathapati, Saginela, Malliboina, & Makineedi, 2012;Nohyneka, Fautzb, BenechKiefferc, & Toutaina, 2004;Sanchez, Handyal, Kannan, Siddalingeshwara, Alvarez-Uria, Gavalda, & Cobella, 2016;Senthilkumaran & Thirumalaikolundusubramania, 2015). It is reported that some commercial hair dyes contain a potent nephrotoxic cocktail containing PPD, propylene glycol, and resorcinol and histological changes of acute tubular necrosis have been described in PPD poisoning (Prabhakar & Kamalakar, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations